Virtual reality-based rehabilitation experience of stroke survivors: a meta-synthesis of qualitative studies - Cai, Jingyi; Liu, Beixue; Song, Mingyang; Wang, Qiuyi; Zhou, Lanshu (Frontiers in Public Health, 2025)
AimTo examine and synthesize qualitative data regarding the experiences of stroke survivors who underwent rehabilitation using virtual reality (VR).MethodsWe critically appraised the included study using the Joanna Briggs Institute Critical Assessment Checklist for Qualitative Research. Relevant qualitative studies were searched in PubMed, EMBASE, CINAHL, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wan Fang Database, China Science and Technology Journal Database, and China Biomedical Literature Database from inception to December 2024. Two researchers independently extracted and analysed the data and integrated the results using a pooled meta-aggregation approach.ResultsSixteen studies (n = 145 stroke survivors) were included. A total of 5 meta-themes, 12 categories, and 38 research results were extracted. The meta-themes included perceived benefits, facilitating factors of using VR, and hindering factors of using VR, changes in the physical and mental health following VR rehabilitation, and suggestions and expectations for VR rehabilitation.ConclusionStroke survivors perceived the benefits and barriers of using VR-based rehabilitation (VRBR); therefore, it is a complex perceptual change for them. They require emotional support from family and peers, professional support from healthcare professionals, and financial support from the government. Moreover, rehabilitation motivation is an important factor that influences utilization. Updating VRBR content and functionality is essential to improve user experience.Systematic review registrationPROSPERO CRD42024504700, https://www.crd.york.ac.uk/PROSPERO/search.